Correlation between HDAC4 enhancer DNA methylation and mRNA expression during palatal fusion induced by all‐trans retinoic acid. Issue 12 (29th August 2018) - Shu, Xuan; Cheng, Hongqiu; Shu, Shenyou; Tang, Shijie; Li, Ke; Dong, Zejun
Abstract: Epithelial‐mesenchymal transformation of the medial edge epithelium is the most crucial process in embryonic palatal fusion. This study aimed to explore the relationship and potential mechanism between enhancer DNA methylation and mRNA expression of histone deacetylase 4 (HDAC4) during palatal fusion induced by maternal exposure to all‐trans retinoic acid (ATRA). Pregnant mice were administered ATRA (70 mg/kg) by gavage at embryonic gestation day 10.5 (E10.5) to establish a cleft palate (CP) model in C57BL/6J mice. Control groups were given an equivalent volume of corn oil. Pregnant mice were dissected at E14.5 (n = 6) to obtain embryonic palates. HDAC4 enhancer DNA methylation data were obtained from a previous MethylRAD‐seq. Methylation‐specific polymerase chain reaction (MSP) and real‐time quantitative PCR were used to quantify enhancer methylation and the mRNA expression level of HDAC4. Enhancer DNA methylation at a non‐CpG site within the HDAC4 gene was hyper‐methylated at E14.5 ( P : 0.011, log2 FC:1.67). The MSP results indicated a similar trend, in agreement with the MethylRAD‐seq results. The change in the HDAC4 expression level was negatively correlated with its enhancer DNA methylation level, at the non‐CpG site, during palatal fusion induced by ATRA. Enhancer DNA methylation of HDAC4 might play an important regulatory role during palatogenesis, especially in embryonic palatal fusion at E 14.5, and may facilitate the development of novel epigenetic biomarkers in the treatment of CP. Abstract : Epithelial‐mesenchymal transformation of the medial edge epithelium is the most crucial process in embryonic palatal fusion. This study aimed to explore the relationship and potential mechanism between enhancer DNA methylation and mRNA expression of histone deacetylase 4 (HDAC4). Enhancer DNA methylation of HDAC4 might play an important regulatory role during palatogenesis, especially in embryonic palatal fusion at E 14.5, and may facilitate the development of novel epigenetic biomarkers in the treatment of CP.